'Treading water but drowning slowly': what are GPs' experiences of living and working with mental illness and distress in England? A qualitative study. Issue 5 (3rd May 2018) - Riley, Ruth; Spiers, Johanna; Chew-Graham, Carolyn A; Taylor, Anna K; Thornton, Gail A; Buszewicz, Marta
Abstract : Objectives: This paper provides an in-depth account of general practitioners' (GPs) experiences of living and working with mental illness and distress, as part of a wider study reporting the barriers and facilitators to help-seeking for mental illness and burn-out, and sources of stress/distress for GP participants. Design: Qualitative study using in-depth interviews with 47 GP participants. The interviews were audio recorded, transcribed, anonymised and imported into NVivo V.11 to facilitate data management. Data were analysed using a thematic analysis employing the constant comparative method. Setting: England. Participants: A purposive sample of GP participants who self-identified as: (1) currently living with mental distress, (2) returning to work following treatment, (3) off sick or retired early as a result of mental distress or (4) without experience of mental distress. Interviews were conducted face to face or over the telephone. Results: The findings report GP participants' in-depth experiences of distress and mental illness with many recollecting their distressing experiences and significant psychological and physical symptoms relating to chronic stress, anxiety, depression and/or burn-out, and a quarter articulating thoughts of suicide. Many talked about their shame, humiliation and embarrassment at their perceived inability to cope with the stresses of their job and/or their symptoms of mental illness. Conclusions: These findings paint a concerning picture of the situation affecting primary care doctors, with participants' accounts suggesting there is a considerable degree of mental ill health and reduced well-being among GPs. The solutions are complex and lie in prevention and provision. There needs to be greater recognition of the components and cumulative effect of occupational stressors for doctors, such as the increasing workload and the clinical and emotional demands of the job, as well as the need for a culture shift within medicine to more supportive and compassionate work environments.